A MULTICHANNEL SEISMIC STUDY OF LITHOSPHERIC FLEXURE ACROSS THE HAWAIIAN-EMPEROR SEAMOUNT CHAIN - Watts, A; Tenbrink, U; Buhl, P; Brocher, T (1985)
Existing models assume that the thickened crust beneath seamounts is the result of a surface volcanic load flexing an elastic plate. New results suggest that flexed oceanic crust beneath the Hawaiian-Emperor seamount chain is underlain by a 4-km thick deep crustal body. We intepret the body as a deep crustal sill complex associated with the tholeiitic stage of volcano building along the chain. © 1985 Nature Publishing Group.